Factors associated with typhoid relapse in the era of multiple drug resistant strains - Ahmad, Kaashif Aqeeb; Khan, Liaqat Hayat; Roshan, Bakht; Bhutta, Zulfiqar Ahmed (The Journal of Infection in Developing Countries, 2011)
Introduction: Typhoid has an estimated global burden of greater than 27 million cases per annum with a clinical relapse rate of 5% to 20%. Despite the large relapse burden, the factors associated with relapse are largely unknown. Methodology: We have followed a protocol for the diagnosis and management of pediatric typhoid since 1988. We report factors associated with relapse of culture-proven enteric fever in 1,650 children presenting to the Aga Khan University Medical Center, Karachi, Pakistan, over a 15-year period. Results: In those infected with multiple drug resistant (MDR) strains, factors associated with subsequent relapse include constipation at presentation and presentation within 14 days of fever onset. Diarrhoea in those children infected with drug sensitive strains had an association with decreased subsequent relapse, as was quinolone therapy. Conclusions: Multiple clinical factors at presentation are associated with subsequent typhoid fever relapse. These factors may be postulated to be associated with subsequent relapse due to alterations in the reticuloendothelial system organism load. These data will be valuable in developing algorithms for clinical follow-up in children infected with MDR enteric fever.